Data, (bio)sensing and (other-)worldly stories from the cycle routes of London - Taylor, Alex (Quantified: Biosensing Technologies in Everyday Life, 2016)
Alex S. Taylor (2016) Data, (bio)sensing and (other-)worldly stories from the cycle routes of London, Quantified, p. 189-209, Cambridge, MA: MIT Press This chapter tells a story of promise, one about London’s bike rental data and how it might be used to re-imagine new figurings of human-machine relations. Experimenting with the relational capacities of (bio)sensing and the proliferation of data-everywhere, the possibilities of other worlds are imagined. Mixtures of data at all scales are thrown together, playing with and testing out a thickening and enlivening of relations, new edges, and making room for difference—for different assemblies of bodies, space and time. Relations are brought into being that might just resist the “agencies of homogenization” (Scott 1998) and that mess about in the unevenness and plurality that makes London vibrant.